Modeling and simulation of human behaviors during vertical emergency evacuation via intelligent fuzzy agents - Hadj Sahraoui, Sami; Mohd Ibrahim, Azhar; Saeed Baqalaql, Odai; Al Mahmud, Suaib (IEEE Explore, 2024)
Effective emergency evacuation planning is crucial for minimizing the impact of disasters on individuals and communities. To improve the efficiency and safety of vertical emergency evacuations, such as those from high-rise buildings or offshore platforms, it is important to understand and model the key behaviors that affect the vertical evacuation process. This research aims to use fuzzy logic and Unity to model and simulate human behaviors during vertical emergency evacuations. For the evacuation modeling two approaches such as with fuzzy logic and without fuzzy logic have been tested. The results show that the intelligent fuzzy agents have greater tendency to choose elevators as exits than stairs. It was also depicted that integration of fuzzy logic in agents augmented the evacuation performance by improving the evacuation time by 17.59%.